Modernization, globalization, and social transformation : essays in honour of Professor Yogendra Singh - Modi, Ishwar, editor; Singh, Yogendra (Jaipur : Rawat Publications, 2012)
With reference to India.
Includes bibliographical references and index.
Keywords: SOCIAL CHANGE -- INDIA; GLOBALIZATION -- SOCIAL ASPECTS -- INDIA; INDIA -- SOCIAL CONDITIONS